Continuous versus intermittent negative pressure wound therapy on diabetic foot ulcerations - Chavali, Pravalika; Reddy, M. Mallikarjuna (International Surgery Journal, 2025)
Background: Among continuous and intermittent negative pressure therapies different clinicians have different choices and different school of thoughts. Very few studies have thrown light on this debate so far. Hence present study was done to know the better therapy in the healing of diabetic foot ulcerations between continuous and intermittent methods for best clinical outcomes. Methods: This current study is a hospital based comparative prospective study. Results: In present study, majority of the study population had wound closure by day 12 (41.4%) followed by day 9 (31%), followed by day 15 (13.8%). The difference between the groups regarding wound closure days distribution was not statistically significant. Conclusions: The current study finds that negative pressure wound therapy (NPWT) therapy has higher rates of wound closure and that, for the healing of diabetic leg ulcers, applying either intermittent or continuous NPWT therapy is preferred for better wound closure rates and good bacterial clearance. No method was shown superior to other in terms of wound healing in diabetic foot ulcer.